Modelling start of oak pollen season in different climatic zones in Spain - García-Mozo, H.; Galan, C.; Aira, M. J. (Agricultural and Forest Meteorology, 2002)
Quercus pollen and meteorological data for several years from eight sites in Spain have been statistically analysed to select the threshold temperature and calculate the mean heat accumulation for predicting the Quercus pollination start in different climatic areas. The growing degree days method, which assumes the daily temperature varies as a sine wave, was used for heat accumulation calculations. Threshold temperatures between 4 and 12 ◦ C were chosen using linear regression equations forced through the origin and their root mean square error (RMSE) of predicted against the observed dates for each observation site. Above the threshold, the average growing degree days (up to 1999) for the studied years was taken as the predictor value. Results showed a relationship between the selected threshold and elevation and a stronger and statistically signiﬁcant correlation between threshold and yearly mean temperature, for each site. Regression analysis indicated that the selected threshold and the calculated heat accumulation were optimum for most of the localities. The validity of the results was tested using the meteorological data for the year 2000 as independent variable and this conﬁrmed that there were only a few days difference between the predicted and observed day of the ﬁrst pollen release for most of the studied localities
Keywords: Aerobiology; oak forest; Phenology; pollen; threshold temperature